Integrating Living Values Education into Indonesian Islamic Schools: An Innovation in Character Building - Hidayatulloh, Taufik; Saumantri, Theguh; Ramdani, Zulmi (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
As a country with a majority Muslim population, Indonesia has strong foundations in religious teachings guiding daily life. However, social changes, technological advances, and globalization present challenges in ensuring character education remains relevant and adaptive. Islamic education in Indonesia is central to shaping individual character based on religious and ethical teachings. This study examines the potential of the Living Values Education (LVE) approach as an innovative mainstream in developing Islamic education in Indonesia. This research is a literature study, involving an in-depth analysis of relevant literature. The study shows that LVE provides a holistic approach covering ethical, moral, social, and emotional aspects. In the context of Islamic education, LVE can strengthen the understanding of religious teachings and associate them with universal virtues. The relevance of LVE lies in educators building learning dynamics based on positive character values. Thus, LVE becomes an innovative alternative in Islamic education, encouraging the creation of intelligent, moral, and creative generations for the nation's future.